Clinical and molecular data in cases of prenatal localized overgrowth disorder: major implication of genetic variants in PI3K‐AKT‐mTOR signaling pathway. (10th March 2022) - Bourgon, N.; Carmignac, V.; Sorlin, A.; Duffourd, Y.; Philippe, C.; Thauvin‐Robinet, C.; Guibaud, L.; Faivre, L.; Vabres, P.; Kuentz, P.
ABSTRACT: Objectives: To describe clinical and molecular findings in a French multicenter cohort of fetuses with prenatal diagnosis of congenital abnormality and suspicion of a localized overgrowth disorder (LOD) suggestive of genetic variants in the PI3K‐AKT‐mTOR signaling pathway. Methods: We analyzed retrospectively data obtained between 1 January 2013 and 1 May 2020 from fetuses with brain and/or limb overgrowth referred for molecular diagnosis of PI3K‐AKT‐mTOR pathway genes by next‐generation sequencing (NGS) using pathological tissue obtained by fetal autopsy. We also assessed the diagnostic yield of amniotic fluid. Results: During the study period, 21 subjects with LOD suspected of being secondary to a genetic variant of the PI3K‐AKT‐mTOR pathway were referred for analysis. Of these, 17 fetuses had brain overgrowth, including six with isolated megalencephaly (MEG) and 11 with hemimegalencephaly (HMEG). Of the six with MEG, germline variants were identified in four cases, in either PIK3R2, AKT3 or MTOR, and a postzygotic PIK3R2 variant was found in the other two cases. Of the 11 with HMEG, a postzygotic  PIK3CA  variant was found in three fetuses with extracerebral features of PIK3CA ‐related overgrowth spectrum, and in seven fetuses with isolated HMEG. No pathogenic variant was identified in the 11 th case with HMEG. Four fetuses with limb overgrowth also had one or more lymphatic malformations (LM) and harbored a postzygotic PIK3CA  variant. NGS on cultured amniocytes performed in 10 cases, of which nine had been found positive on analysis of pathological fetal tissue, showed variants in four, in either PIK3CA, PIK3R2 or AKT3 . Conclusions: Isolated MEG or HMEG may lead to identification of genetic variants in the PI3K‐AKT‐mTOR signaling pathway. Cases of limb overgrowth and LM or isolated HMEG are likely associated with PIK3CA variants. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.